Study on Deformation Characteristics of Segment Joints of the Immersed Tunnel in Hong Kong-Zhuhai-Macau Bridge - Yapeng Niu; Yongli Xie; Hongguang Zhang; Xiabing Yue; Yingguang Han; Zhinan Hu (Advances in Materials Science and Engineering)
The segmental joints are the weak parts of the immersed tunnel structure, and their deformation characteristics are closely correlated with the waterproof behavior and structural safety of the whole tunnel. In order to study the deformation characteristics of the segmental joints of immersed structure, in this paper, the E13 pipe section in the natural foundation section of an immersed tunnel in the Hong Kong-Zhuhai-Macao Bridge is taken as the research object, and the model test of the immersed tunnel is carried out. The similarity ratio of the model to the prototype is determined according to the actual engineering scale and the capability of the model test system, and the plexiglass is selected as the model material of the immersed tunnel according to the similarity of elastic modulus and density. In the test, various working conditions, including back-silting load and different prestress control values, are analyzed, and the influence of settlement and opening of the immersed tunnel is obtained, along with the stress-strain characteristics of the segment joints. Results show that the increase of the back-silting load will increase the element settlement and the expansion of the segment joints, but the application of prestress increases the overall stiffness of the element, which can effectively restrain the settlement of element and the expansion of joints. Furthermore, based on the model test conditions, a finite element model is established to simulate the mechanical behavior of the immersed tunnel. The settlement curve and stress-strain curve of the numerical analysis are found to be similar to those obtained from the model test, which verifies the reliability of the model test.